Translation, cross-cultural adaptation and validation of the Persian version of selected PROMIS measures for use in lumbar canal stenosis patients - Oskouie, Iman M.; Rostami, Mohsen; Moosavi, Mersad; Zarei, Mohammad; Jouibari, Morteza Faghih; Ataie, Hosienali; Jafarieh, Arash; Moghadam, Navid; Kordi, Ramin; Khadivi, Masoud; Mazloumi, Adel (Journal of Education and Health Promotion, 2023)
The National Institutes of Health (NIH) developed a new measurement system called the Patient-Reported Outcomes Measurement Information System (PROMIS) which can be used for multiple health conditions. The 29-item short form (PROMIS-29) with seven domains was more often used by clinical researchers to measure the physical function, mood and sleeping status of patients with low back pain (LBP). Translation of the PROMIS into multiple languages and adaptation of its application in different cultural diversities can help to further standardize clinical research studies and make them comparable to each other. This study aimed to cross-culturally adapt the PROMIS-29 into Persian (P-PROMIS-29) and evaluate the construct validity and reliability of the translated questionnaire among patients with lumbar canal stenosis. The translation was conducted by using the multilingual translation methodology guideline. Construct validity, internal consistency, and test-retest reliability at a two-week interval for the P-PROMIS-29 were calculated. Construct validity was assessed by calculating correlations between the P-PROMIS-29 with Oswestry Disability Index (ODI) and Roland-Morris results. The study sample included 70 participants with lumbar canal stenosis. Internal consistencies were moderate to good with Cronbach's alpha ranging from 0.2 to 0.94. The test-retest reliability evaluation was excellent with intraclass correlation coefficients (ICCs) ranging from 0.885 to 0.986. Construct validity of different domains of P-PROMIS-29 were moderate to good, with Pearson's correlation coefficient results ranging from 0.223 to 0.749. Our results showed that P-PROMIS-29 is a valid and reliable measurement tool for evaluation of patients with lumbar canal stenosis.